2011
DOI: 10.1016/j.ygyno.2010.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of laparoscopy versus laparotomy in early stage endometrial cancer: A randomised trial

Abstract: Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…As a result of shorter hospitalization, for many patients, total laparoscopic hysterectomy (TLH) is likely to be more cost effective to society than TAH in terms of incremental costs per complication-free patient—however, this may not be the case in obese patients with BMI > 35 due to high laparotomy conversion rates [9, 10]. Robot assisted total laparoscopic hysterectomy (TRH) is an increasingly available alternative that may confer an advantage in obese and other complex patients by lowering the need for conversion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of shorter hospitalization, for many patients, total laparoscopic hysterectomy (TLH) is likely to be more cost effective to society than TAH in terms of incremental costs per complication-free patient—however, this may not be the case in obese patients with BMI > 35 due to high laparotomy conversion rates [9, 10]. Robot assisted total laparoscopic hysterectomy (TRH) is an increasingly available alternative that may confer an advantage in obese and other complex patients by lowering the need for conversion.…”
Section: Introductionmentioning
confidence: 99%
“…30 This study has not investigated the cost implications of the TLRH compared to the RAH. However, we have shown that the TLRH is a surgically safe procedure in obese women when performed by an experienced surgical and anesthetic team with the appropriate equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Using methods described in the companion paper, the PPRTF compared the current ("status quo") costs of care to the costs that might be incurred in various alternative ("optimal") scenarios [14]. Three potential areas of cost savings were examined: increasing the rate of minimally invasive hysterectomy; reducing length of stay; and decreasing readmissions/emergency department visits [15][16][17][18][19][20][21][22]. The PPRTF modeled a scenario incorporating favorable changes in all three parameters.…”
Section: Summary Of Ecap Development and The Centers For Medicare Andmentioning
confidence: 99%